2009 summer sightings of common dolphin (Delphinus delphis) in the Ionian Islands. - PAPALE, ELENA; GIACOMA, Cristina; GALLI A.; ANICHINI M.; AZZOLIN M. (Federal maritime and hydrographic agency, 2010)
During the months of July and August 2008 and 2009, vessel based surveys were carried out in Northern Ionian Islands waters, in order to asses the occurrence and distribution of cetacean species in relation to ecological and anthropogenic parameters. Surveys were carried out aboard a 12 m sailing vessel, covering an area of about 3.500 square km, located between Northern Kerkira and Northern Cephalonia, and characterized by a massive presence of pleasure boats during the summer. A total of about 2.000 nautical miles were travelled looking for cetaceans. Four species were sighted during the period of study, for a total of 29 sightings with a single species and 1 with mixed group, more in detail: bottlenose dolphin (Tursiops truncatus) 17 sightings, striped dolphin (Stenella coeruleoalba) 5 sightings, common dolphin (Delphinus delphis) 3 sightings, and fin whale (Balaenoptera physalus) 5 sightings. While during 2008 none of the recorded sightings regarded common dolphin, in 2009 the 21,43% of them reported the presence of the species in the study area: 2 sightings in single species groups and in 1 sighting in a mixed group with striped dolphins. Just one sighting was located in the area were the species was reported to be common before its drastic reduction of the last years. The other 2 sightings were located in the waters between the Islands of Kerkira and Paxos. During all common dolphins sightings calves presence was documented. The mean sighting frequency for the endangered species was of 0,01 (sightings/monitored hours). 2009 results highlight the need of investigate the movement of the species on a large scale in order to find how the distribution and the habitat use could have changed from previous years, as a reaction of prey reduction and of increasing boat traffic in the area comprised by Lefkada and the mainland.